Circulatory TGF- β1 is significantly higher in early stage of pulmonary sarcoidosis - Mirsaeidi, Mehdi; Omar, Hesham R; Calzadilla, Andrew; El khatib, Ahmad; Whitney, Philip; Sweiss, Nadera; Culver, Daniel; Campos, Michael; Baughman, Robert; Machado, Roberto (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Introduction: The pathogenesis of pulmonary fibrosis in sarcoidosis is not known. We hypothesized that higher levels of circulatory growth factors are present in early stages of pulmonary sarcoidosis and may be associated with pulmonary fibrosis. Methods: Age and sex-matched subjects with sarcoidosis stage 0-1 (n=18), stage 4-5 (n=13) and healthy controls (n=5) had their serum TGF-β1, FGF, and VEGF levels measured as well as their gene expressions determined in peripheral blood mononuclear cells. Results: TGF-β1 levels were significantly higher in patients with stage 0-1 sarcoidosis compared with normal healthy control patients (25,488 vs. 13800 pg/ml, P=0.05). Patients with sarcoidosis stage 4 had a 1.3-fold higher peripheral blood mononuclear cells (PBMC) gene expression of TGF-β1 compared with subjects at stage 0-1 (P= 0.041). The serum levels of FGF, and VEGF had a trend towards higher levels in sarcoidosis subjects compared to normal controls. Conclusion: These results suggest that cell growth factors levels are high in early stages of sarcoidosis. These findings should be validated in larger studies.